2012
DOI: 10.1016/j.cell.2012.10.037
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific Silencing of Regulatory Elements as a Mechanism of X Inactivation

Abstract: The inactive X chromosome’s (Xi) physical territory is microscopically devoid of transcriptional hallmarks and enriched in silencing-associated modifications. How these microscopic signatures relate to specific Xi sequence is unknown. Therefore, we profiled Xi gene expression and chromatin states at high resolution via allele-specific sequencing in mouse trophoblast stem cells. Most notably, X-inactivated transcription start sites harbored distinct epigenetic signatures relative to surrounding Xi DNA. These si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
214
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(246 citation statements)
references
References 45 publications
22
214
2
Order By: Relevance
“…Moreover, although biochemical analysis indicates that Xist and PRC2 directly interact (7,29,30) and it is known that they nucleate together at the Xic (8), whether Xist and PRC2 stay together as they spread along the Xi has not been answered definitively by epigenomic analyses (10,11,15). Additionally, a recent analysis using 3D-SIM with 100-nm resolution suggested that Xist RNA and PRC2 are spatially separated on the Xi, to a degree that called into question the idea that Xist recruits PRC2 to the Xi (20).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, although biochemical analysis indicates that Xist and PRC2 directly interact (7,29,30) and it is known that they nucleate together at the Xic (8), whether Xist and PRC2 stay together as they spread along the Xi has not been answered definitively by epigenomic analyses (10,11,15). Additionally, a recent analysis using 3D-SIM with 100-nm resolution suggested that Xist RNA and PRC2 are spatially separated on the Xi, to a degree that called into question the idea that Xist recruits PRC2 to the Xi (20).…”
Section: Resultsmentioning
confidence: 99%
“…The unexpectedly low number of Xist transcripts led us to question how Xist can target PRC2 so broadly to the Xi, resulting in the chromosome-wide enrichment of H3K27me3 as demonstrated by ChIP-seq analysis (11,15) and by conventional microscopic techniques (7,9,12,13,17,28). Moreover, although biochemical analysis indicates that Xist and PRC2 directly interact (7,29,30) and it is known that they nucleate together at the Xic (8), whether Xist and PRC2 stay together as they spread along the Xi has not been answered definitively by epigenomic analyses (10,11,15).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work pioneered by studies on X-chromosome inactivation has highlighted a central role for long non-coding RNAs (lncRNAs) in epigenetic silencing and enhancer activation (Calabrese et al 2012). Enhancer RNAs (eRNAs) are a class of lncRNAs with a potential role in the mediation of epigenetic modifications as well as interactions with TFs (Gupta et al 2010, Kogo et al 2011, Calabrese et al 2012.…”
Section: Functional Role Of Non-coding Rna In Nr Signallingmentioning
confidence: 99%
“…47 A recent study suggests that the number of mouse escape genes can be higher than previously thought, depending on the cell type. 48 Thus, in females, the number of escape genes (i.e., degree of escape) is variable in each tissue.…”
Section: Chromosome Inactivation Escape Genes In Femalesmentioning
confidence: 99%